Pathological characteristics of reoperated regrowing clinically nonfunctioning pituitary tumor cases in comparison with initial surgical cases - Ishida, Atsushi; Inoshita, Naoko; Tanabe, Noriaki; Takano, Koji; Tanaka-Mizuno, Sachiko; Kato, Masataka; Yoshimoto, Haruko; Shiramizu, Hideki; Matsuoka, Go; Yamada, Shozo (Frontiers in Endocrinology, 2024)
Objective Postoperative nonfunctioning pituitary tumor (NFPT) regrowth is a significant concern, but its predictive factors are not well established. This study aimed to elucidate the pathological characteristics of NFPTs indicated for reoperation for tumor regrowth. Methods Pathological, radiological, and clinical data were collected from patients who underwent repeat operation for NFPT at Moriyama Memorial Hospital (MMH) between April 2018 and September 2023. For comparison, we also gathered data from patients who underwent initial surgery for NFPT during the same period at MMH. Results Overall, 61 and 244 NFPT patients who respectively underwent reoperation and initial operation were evaluated. The mean period between the previous operation and reoperation was 113 months. Immunonegativity for any adenohypophyseal hormone was significantly more frequent in the reoperation group than in the initial operation group. In addition, the rate of hormone-negative but transcription factor–positive (H-/TF+) tumors among silent gonadotroph tumors was significantly higher in the reoperation group than in the initial operation group. Furthermore, seven silent corticotroph tumors (SCTs) in the reoperation group were ACTH-negative but TPIT-positive. Because most of the previous surgeries were performed in other hospitals a long time ago, we could procure the previous pathological results with immunohistochemistry (IHC) only from 21 patients. IHC for TF had not been performed in all the previous specimens. IHC for adenohypophyseal hormone was almost the same as the current results, and many H-/TF+ tumors were previously diagnosed as NCT. In addition, the reoperated patients were classified into 3 groups on the basis of the condition of the previous operation: gross total resection (GTR), 12 patients; subtotal resection (STR), 17 patients; and partial resection (PR), 32 patients. The mean Ki-67 LI in the GTR, STR, and PR subgroups were 1.82, 1.37, and 0.84, respectively, with the value being significantly higher in the GTR subgroup than in the PR subgroup (P < 0.05). Conclusions The ratio of H-/TF+ tumors is significantly higher in symptomatically regrown tumors than in the initial cases, which used to be diagnosed as NCT. PR cases tend to grow symptomatically in a shorter period, even with lower Ki-67 LI than GTR cases.